Metal–organic frameworks: a universal strategy towards super-elastic hydrogels. Issue 18 (3rd April 2019) - Liu, Huaizhi; Peng, Hao; Xin, Yumeng; Zhang, Jiuyang
Abstract : We reported for the first time using metal–organic framework (MOF) nanoparticles as effective nanofillers to significantly enhance the mechanical performance of hydrogels. The MOF hydrogels have been developed for drug delivery materials with high loading capacity and much extended drug releasing profiles. Abstract : Hydrogels, as important soft materials, have promising applications in many fields such as biomedicines, biomimetic materials, and smart devices. However, their weak mechanical properties restrict their further application. Here, we report for the first time using metal–organic frameworks (MOFs) as effective nanofillers to significantly enhance the mechanical performance of hydrogels. With 5 wt% (weight percent) MOF nanofillers, the hydrogel was extremely toughened by 13.2 times (635.2 kJ m −3 ) compared with neat hydrogels (47.8 kJ m −3 ). Such MOF-hydrogels exhibited phenomenal elasticity, i.e., they remained stable even when crushed by a car. The breaking strain ( ε ) of the MOF-hydrogel could achieve as high as 2060% with superior mechanical stability (stable over 1000 compressive cycles). It is interesting that all types of MOFs in the studies including ZIF-8 ( ε : 2060%), UiO-66 ( ε : 1640%), and ZIF-67 ( ε : 2000%) are capable of strengthening the hydrophilic networks. The polar groups and cationic metal centers on the surface of MOFs are attributed to the toughening effects of hydrogels. Additionally, the highly porous structure of MOFs makes the MOF-hydrogels promising candidates for drug delivery materials with high loading capacity and much extended releasing profiles. This work provides new insight into creating antifatigued hydrogels via nanoporous MOFs, which combines the merits of MOFs and hydrogels.